Efectividad de la fototerapia en la ictericia neonatal. Hospital Provincial General Docente. Riobamba, 2021 - Alulema Guachilema, Gabriela Patricia (2022)
ABSTRACT: Introduction: Neonatal jaundice is a clinical sign considered as a physiological process generated by hepatic immaturity and high production of bilirubin; in Ecuador, between 2014 and 2017, 28,865 cases of neonatal jaundice were reported, subdivided into physiological and pathological, being the second cause of infant morbidity. Objective: The main objective of the research is to determine the effectiveness of Phototherapy in patients with neonatal jaundice at the General Teaching Hospital of the city of Riobamba in the period January - August 2021. Methodology: This study is descriptive with a cross-sectional design; retrospectively, the information will be synthesized through the data matrix, taking 123 newborns with neonatal jaundice as a sample. Results: 83% were born at term, 57% were women, 7% presented macrosomia and 77% adequate weight for gestational age, 93% of the newborns presented values greater than 10 mg / dL at admission; 63% of the cases showed hyperbilirubinemia before 24 hours of life, and the time of exposure to Phototherapy was less than three days in 79.7%. Conclusions: A statistically significant relationship (p = 0.0000) was identified between treatment with Phototherapy in neonatal jaundice and bilirubin levels; therefore, we affirm that there is a positive correlation between Phototherapy and the decrease in bilirubin levels.